Analysis of Morphological Traits of Geographically Separated Population of Indigenous Muscovy Duck (Cairina Moschata) - Ogah, D.M. (International Journal of Poultry Science, 2009)
Inter and intra specific variation among muscovy duck ecotypes from three agroecological zones of Nigeria were studied The work evaluate the morphological variation of three ecotypes ( rainforest ecotypes, humid or guinea savanna and dry savanna ecotypes) covering southern or coastal region, central and northern part of Nigeria. Twelve morphological traits including weight were considered. Significant (p